Analisis Peran Lurah dalam Upaya Mengatasi Pola Komunikasi Spiral of Silence di Kantor Kelurahan Menteng Kota Palangka Raya: Analysis of the Village Head's Role in Addressing the Communication Pattern of the Spiral of Silence at the Menteng Sub-District Office, Palangka Raya City - Lisnawati, Lisnawati; Averina, Laurencia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Spiral of Silence Communication is a communication pattern where someone has opinions about various issues but is hesitant and afraid to express them because they are afraid of feeling protected, which causes these opinions to be neither open nor closed. The spiral of silence theory discusses issues regarding minority groups. The aim of this research is to find out how the village head plays a role in overcoming the spiral of silence communication pattern at the Menteng Village Office, Palangka Raya City. This research uses qualitative methods by conducting interviews and observations. There were three informants in this study. The results of this research show that the village head at the Menteng Subdistrict Office plays a significant role in efforts to overcome the Spiral of Silence communication pattern, this can be seen from the 4 indicators that have been fulfilled, including being a communicator, problem solver, resource liaison and communicator.